Peningkatan Kualitas Pelayanan (SERVQUAL) Pada World Fit Gym Kota Bekasi - Darmawan, Imam; Dwita, Febrisi (JURNAL MAHASISWA BINA INSANI; Vol 8 No 2 (2023): Jurnal Mahasiswa Bina Insani (November 2023), 2023)
This research aims to evaluate the implementation of service quality at World Fit Gym in Bekasi City. The research method uses descriptive analysis with a qualitative approach, this research collects data from gym members through data triangulation, such as observation, in-depth interviews, and documentation, which includes measuring tangibles, Reliability, Responsiveness, Assurance, and Empathy to see the quality of service provided by World Fit Gym. The results of the analysis show that the majority of members are satisfied with the quality of service provided, but there are some areas that require further improvement. Improvements in a more consistent class schedule and more routine maintenance of gym equipment were identified as important factors to increase member satisfaction. This study suggests that World Fit Gym management focuses on continuous training for instructors, increased frequency of cleaning, and improved technology systems for booking and payment rooms. Implementation of these recommendations is expected to increase member loyalty and the gym's competitiveness in an increasingly competitive fitness market.